Piezoelectric biosensors: shedding light on principles and applications - Skládal, Petr (Mikrochimica acta, 2024)
The three decades of experience with piezoelectric devices applied in the field of bioanalytical chemistry are shared. After introduction to principles and suitable measuring approaches, active and passive methods based on oscillators and impedance analysis, respectively, the focus is directed towards biosensing approaches. Immunosensing examples are provided, followed by other affinity sensing approaches based on hybridization of nucleic acids, aptamers, monitoring of enzyme activities, and detection of pathogenic microbes. The combination of piezosensors with cell lines and testing of drugs is highlighted, including mechanically active cells. The combination of piezosensors with other measuring techniques providing original hybrid devices is briefly discussed.
Keywords: Nucleic Acids; Enzyme activity; buněčné linie; Microbial detection; nukleové kyseliny; elektrická impedance; Quartz crystal microbalance; Cell Line; oligonukleotidy; Electric Impedance; Combined biosensing set-ups; Immunosensors; Cellular biosensors; Oligonucleotides